The Research of the Radial Growth of the Flora Species Which Do Not Have Special Protection on the South Hillsides of Greater Caucasus - Aliyev, Prof. RAE. Z.H. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2020)
The radial growth of the trunks of the following flora species which do not have special protection on the southern hillsides of Greater Caucasus was studied in the article: Georgioan oak- Quercus iberica M.Bieb Common hornbeam - Caprinus betulus L. Common chestnut - Castanea sativa Mill. Black walnut - Juglans nigra L., Heart leaved alder - Alnus subcordata C.A.Mey. During the dendrochronological analyses, the dynamics of growth over the years were analysed based on the distances between the tree rings. The impact of the climatic factors on the growth of the trees was analysed and the ages of tree species were investigated. Based on the dendrochronological historical application, according to the numbers of tree rings, the ages of the trees were defined in the studied species. According to the numbers of tree rings, the oldest type of the rare and scanty flora types which have no special protection was identified as Caprinus betulus L. in the Zagatala region. The tree was taken from Zagatala district, planted in 1944, was 75 years old and had 330 cm diameter. The observation of dendrochronological researches indicates the formation of a new microclimate. It was observed that in the investigated species, radial growth was more intense during matureness, then it was weakened with age. In the comparative analysis, it was observed that the minimum radial growth was in 2010 and 2015, and the maximum growth was between 1973 and 1985 in the Zagatala region